A review of the botany, phytochemistry, pharmacology, synthetic biology and comprehensive utilization of Silybum marianum - Zhang, Xiaozhuang; Liu, Meiqi; Wang, Zhen; Wang, Panpan; Kong, Lingyang; Wu, Jianhao; Wu, Wei; Ma, Lengleng; Jiang, Shan; Ren, Weichao; Du, Likun; Ma, Wei; et al. (Frontiers in Pharmacology, 2024)
Silybum marianum (L.) Gaertn, a herbaceous plant with a long history in traditional medicine for the treatment of hepatobiliary diseases, particularly in Europe, which has attracted attention for its remarkable therapeutic effect. This review systematically summarizes the research progress in the botany, phytochemistry, pharmacology, comprehensive utilization and synthetic biology of S. marianum. Up to now, more than 20 types of flavonolignan components have been isolated from S. marianum. In addition, the rearch on fatty acids and triterpenoids is also constantly improving. Among them, silybin is the most active compound in flavonolignans components. Its pharmacological effects in vivo and in vitro include anti-inflammatory, antioxidant, anti-tumour, hypoglycaemic, neuroprotective and immunoregulatory properties. The use of coniferyl alcohol and taxifolin as substrates to produce silybin and isosilybin under the action of enzyme catalysis is the commonly used biosynthetic pathway of silymarin, which provides support for a comprehensive analysis of the synthetic pathway of silymarin. In addition to medicinal use, the extracts of plants also have broad application prospects in the production of food, health care products, cosmetics and other aspects. In addition, the chemical composition, pharmacological mechanism and synthetic biology of S. marianum need to be further studied, which is very important for its clinical efficacy and resource development.